The art of hunger - Auster, Paul, 1947- (New York, NY : Faber and Faber, 1998)
Paul Auster traces the complusion to make literature -or art- through the essays on Kafka, Beckett, Celan, Hamsun and other seminal figures of our century.
Keywords: American essays; Essays, American